A material for hot-corrosion resistant centrifugal compressor impellers and a method for making the same

CN122978802APending Publication Date: 2026-10-27TI LINGTE COMPRESSOR WUXI CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610860953.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-15
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0003]在实际工作过程中,叶轮长期处于高速旋转状态,并且同时伴随着高温、高湿度和腐蚀等恶劣工况,极易使叶轮产生腐蚀等失效形式,严重影响了离心压缩机的使用寿命和工作性能,目前保护叶轮表面性能的途径可利用防护涂层,包括无机、有机或复合涂层,环氧树脂由于其优异的机械性能、附着力和耐磨性,是金属防护中常用的涂层材料,其中水性环氧树脂涂料相较于溶剂型环氧树脂涂料因其绿色环保性而备受关注,但其在与固化剂的交联反应中容易在环氧树脂涂层表面形成微孔,产生的孔隙会严重影响环氧树脂阻隔介质的能力,从而引发腐蚀,且环氧树脂作为防护涂层本身脆性大,在冲击作用下容易出现开裂或剥落,耐腐蚀性能及耐高温性能也需进一步提升

Benefits of technology

本发明采用水热共沉淀法制备得到镁铝层状双金属氢氧化物,同时利用丹皮酚与环氧氯丙烷发生亲核取代反应制备环氧改性丹皮酚,然后利用3-氨丙基三乙氧基硅烷、三聚甲醛和环氧基丹皮酚为原料通过曼尼希反应合成环氧改性有机硅曼尼希碱,随后利用环氧改性有机硅曼尼希碱分子结构中硅氧烷基水解后与镁铝层状双金属氢氧化物表面羟基发生脱水缩合,制备得到改性镁铝层状双金属氢氧化物作为树脂基体功能改性的二维填料,再加入八氨苯基POSS与改性镁铝层状双金属氢氧化物中引入的环氧基反应,制备得到复合功能性填料。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application relates to the field of functional materials and discloses a heat-cracking-resistant centrifugal compressor impeller material and a preparation method thereof, which comprises an impeller base material and a functional coating, and the functional coating comprises water-based epoxy resin, composite functional fillers, modified isophorone diamine curing agent and additives; the composite functional fillers are prepared by grafting epoxy-modified organosilicon Mannich base with magnesium-aluminum layered double hydroxide and ring-opening reaction with octaaminophenyl POSS; the epoxy-modified organosilicon Mannich base is prepared by Mannich reaction of epoxy-modified paeonol prepared by reaction of paeonol and epichlorohydrin, 3-aminopropyl triethoxysilane and trioxane; and the modified isophorone diamine curing agent is prepared by taking diethylene glycol, isophorone diisocyanate, glutaric acid and isophorone diamine as raw materials; the functional coating prepared by the application has high adhesion, high hardness and strong impact resistance, and simultaneously has good hydrophobicity, corrosion resistance and heat-cracking resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of functional materials technology, specifically relating to a thermal crack resistant centrifugal compressor impeller material and its preparation method. Background Technology

[0002] Centrifugal compressors, with their significant advantages such as high single-stage pressure ratio and wide operating range, have been widely used in many fields such as petrochemicals, air energy storage, industrial transportation, and aerospace. The impeller is the core component of a centrifugal compressor. When the impeller rotates at high speed, a low-pressure zone is generated in the channel between the blades, drawing in fresh air from the intake duct. Driven by the impeller blades, the air is thrown from the center of the impeller to the edge. In this centrifugal process, the speed and pressure of the air increase sharply. Its function is to convert the rotational mechanical energy transmitted by the turbine into the pressure energy and thermal energy of the intake working fluid through aerodynamic principles, so as to achieve the core goal of providing high-density, high-quality flow intake air for the engine.

[0003] In actual operation, the impeller is constantly rotating at high speed, and is subjected to harsh conditions such as high temperature, high humidity, and corrosion. This makes the impeller highly susceptible to corrosion and other failure modes, severely affecting the service life and performance of the centrifugal compressor. Currently, protective coatings, including inorganic, organic, or composite coatings, can be used to protect the surface properties of the impeller. Epoxy resin is a commonly used coating material for metal protection due to its excellent mechanical properties, adhesion, and wear resistance. Among them, water-based epoxy resin coatings have attracted much attention due to their green and environmentally friendly nature compared to solvent-based epoxy resin coatings. However, during the cross-linking reaction with the curing agent, micropores are easily formed on the surface of the epoxy resin coating. The resulting pores will seriously affect the ability of epoxy resin to block the medium, thus causing corrosion. In addition, epoxy resin itself is brittle as a protective coating and is prone to cracking or peeling under impact. Its corrosion resistance and high temperature resistance also need to be further improved. Summary of the Invention

[0004] To address the shortcomings mentioned in the background art, the present invention aims to provide a thermal crack resistant centrifugal compressor impeller material and its preparation method. By adding composite functional fillers and modified isophorone diamine curing agents, a functional coating is prepared on the surface of the impeller substrate with high adhesion, strong hardness and impact resistance, hydrophobic properties, and good corrosion resistance and thermal crack resistance.

[0005] The objective of this invention can be achieved through the following technical solutions: A thermal crack resistant centrifugal compressor impeller material includes an impeller substrate and a functional coating applied to the surface of the impeller substrate. The functional coating comprises the following components in parts by weight: 60-75 parts of waterborne epoxy resin, 9-15 parts of composite functional filler, 6-14 parts of modified isophorone diamine curing agent, 0.3-1 part of wetting agent, 0.2-0.7 parts of defoamer, and 0.2-0.8 parts of leveling agent. The composite functional filler is prepared by grafting epoxy-modified organosilicon Mannich base with magnesium-aluminum layered bimetallic hydroxide, and then reacting the prepared modified magnesium-aluminum layered bimetallic hydroxide with octaaminophenyl POSS in a ring-opening reaction. The epoxy-modified organosilicon Mannich base is prepared by nucleophilic substitution reaction of paeonol with epichlorohydrin, and then prepared by Mannich reaction using 3-aminopropyltriethoxysilane, trioxymethylene and epoxy paeonol as raw materials. The modified isophorone diamine curing agent is prepared by nucleophilic addition reaction of diethylene glycol and isophorone diisocyanate, followed by polyesterification reaction of the prepared terminal hydroxyl intermediate with glutaric acid to prepare terminal carboxyl low polyester, and then amidation reaction of terminal carboxyl low polyester with isophorone diamine.

[0006] Preferably, the impeller substrate is made of one of aluminum alloy, stainless steel, titanium alloy, and nickel alloy.

[0007] Preferably, the preparation method of the composite functional filler includes the following steps: A. Dissolve magnesium chloride and aluminum nitrate nonahydrate in deionized water to obtain a salt solution. Prepare an alkali solution using anhydrous potassium carbonate and deionized water. Slowly add the alkali solution to the salt solution and reflux at 100℃ and 300~400r / min for 10h. Adjust the pH value at the titration endpoint to 8~11 by controlling the amount of alkali solution. After the reaction is completed, centrifuge, wash and dry to prepare magnesium-aluminum layered bimetallic hydroxide. B. Add paeonol, epichlorohydrin and benzyltriethylammonium chloride to the reactor, purge the air from the reaction system with nitrogen, heat to 100°C under stirring and react for 4 hours, then cool to 60°C, add solid sodium hydroxide in batches over 1 hour and continue the reaction for 4 hours. After the reaction is completed, wash with water until neutral, and distill under reduced pressure to prepare epoxy-modified paeonol. C. Under nitrogen protection, 3-aminopropyltriethoxysilane, trioxymethylene, epoxy paeonol and anhydrous ethanol were added to the reactor. The pH of the solution was adjusted to 5 using 15% hydrochloric acid. The temperature was raised to 60℃ and the reaction was continued for 6 hours. After the reaction was completed, the solution was distilled under reduced pressure and recrystallized to prepare epoxy-modified organosilicon Mannich base. D. Add magnesium-aluminum layered bimetallic hydroxide and epoxy-modified organosilicon Mannich base to a mixed solution of anhydrous ethanol and deionized water, and stir at 65-80℃ for 6-8 hours. After the reaction is completed, filter, wash and dry to prepare modified magnesium-aluminum layered bimetallic hydroxide. E. Add modified magnesium-aluminum layered bimetallic hydroxide and octaaminophenyl POSS to the reactor, then add dehydrating agent N,N'-dicyclohexylcarbodiimide, catalyst benzyltriethylammonium chloride and N,N-dimethylacetamide solvent. Stir and react at 140°C for 24 h in a nitrogen atmosphere. After the reaction is completed, filter, wash and dry to prepare composite functional filler.

[0008] Preferably, in step A, the molar ratio of magnesium ions to aluminum ions in the salt solution is 1~3:1; and the mass ratio of anhydrous potassium carbonate to deionized water in the alkaline solution is 1:5~6.

[0009] Preferably, in step B, the molar ratio of paeonol, epichlorohydrin, and benzyltriethylammonium chloride is 1:1:0.0142; and in step C, the molar ratio of 3-aminopropyltriethoxysilane, paraformaldehyde, and epoxypaeonol is 1:1.3:1.

[0010] Preferably, in step D, the mass ratio of magnesium-aluminum layered bimetallic hydroxide to epoxy-modified organosilicon Mannich base is 10:1~3; and in step E, the mass ratio of modified magnesium-aluminum layered bimetallic hydroxide to octaaminophenyl POSS is 10:3~5.

[0011] Preferably, the preparation method of the octaaminophenyl POSS includes the following steps: (1) Add fuming nitric acid to the reactor, slowly add octaphenyl POSS under ice bath, react at 0°C for 30 min, then pour the reaction solution into ice water to obtain a pale yellow precipitate, filter, wash with water until neutral, freeze dry to prepare octanitrophenyl POSS; (2) Add octanitrophenyl POSS and palladium on carbon to the reactor, add tetrahydrofuran under nitrogen atmosphere, heat to 60℃ and react for 30 min, then slowly add hydrazine hydrate and continue the reaction for 12 h. After the reaction is completed, filter with diatomaceous earth, concentrate the filtrate and add it to deionized water to obtain a white precipitate, filter and freeze dry to prepare octanitrophenyl POSS.

[0012] Preferably, the preparation method of the modified isophorone diamine curing agent includes the following steps: ① Diethylene glycol and xylene were added to the reactor, and after stirring and mixing, isophorone diisocyanate was slowly added dropwise. The mixture was stirred at 80°C for 4 hours. After the reaction was completed, the solvent was removed by rotary evaporation to prepare the terminal hydroxyl intermediate. ② Add the terminal hydroxyl intermediate and glutaric acid to the reactor, stir and react at 125~135℃ for 6~7h. After the reaction is completed, take out the product and place it in a vacuum oven to remove moisture, and prepare terminal carboxyl low polyester. ③ Add carboxyl-terminated low-polyester and xylene to the reactor, stir and mix, then heat to 60°C, slowly add isophorone diamine, then heat to 80°C and react for 3 hours. After the reaction is complete, heat to 150~180°C and reflux to separate water. After anhydrous distillation, remove solvent under reduced pressure to prepare modified isophorone diamine curing agent.

[0013] Preferably, in step ①, the molar ratio of diethylene glycol to isophorone diisocyanate is 2.2~2.5:1; in step ②, the molar ratio of terminal hydroxyl intermediate to glutaric acid is 1:1.3; and in step ③, the mass ratio of terminal carboxyl oligoester to isophorone diamine is 0.8~1:1.

[0014] The preparation method of the heat-crack resistant centrifugal compressor impeller material as described above includes the following steps: weighing each component according to weight parts, thoroughly mixing the water-based epoxy resin, composite functional filler, wetting agent, and leveling agent, then adding the modified isophorone diamine curing agent and defoamer and mixing to obtain a functional coating, then coating the functional coating onto the surface of the impeller substrate and curing it to obtain the heat-crack resistant centrifugal compressor impeller material; the wetting agent is polydimethylsiloxane; the leveling agent is sodium polyacrylate; and the defoamer is fatty alcohol polyoxyethylene ether or alkylphenol polyoxyethylene ether.

[0015] The beneficial effects of this invention are: This invention employs a hydrothermal co-precipitation method to prepare magnesium-aluminum layered bimetallic hydroxides. Simultaneously, an epoxy-modified paeonol is prepared by a nucleophilic substitution reaction between paeonol and epichlorohydrin. Then, an epoxy-modified organosilicon Mannich base is synthesized via the Mannich reaction using 3-aminopropyltriethoxysilane, trioxymethylene, and epoxy-based paeonol as raw materials. Subsequently, the siloxane groups in the epoxy-modified organosilicon Mannich base are hydrolyzed and undergo dehydration condensation with the hydroxyl groups on the surface of the magnesium-aluminum layered bimetallic hydroxide to prepare a modified magnesium-aluminum layered bimetallic hydroxide, which serves as a two-dimensional filler for functional modification of the resin matrix. Finally, octaaminophenyl POSS is added to react with the epoxy groups introduced into the modified magnesium-aluminum layered bimetallic hydroxide to prepare a composite functional filler.

[0016] Surface grafting of epoxy-modified organosilicon Mannich base improves the compatibility and dispersibility of magnesium-aluminum layered bimetallic hydroxide with the resin matrix, enhances the interfacial interaction, and provides the modified magnesium-aluminum layered bimetallic hydroxide with good resistance to corrosive media penetration and its "maze effect," which can prolong the diffusion path of corrosive media in the coating. Furthermore, the octaaminophenyl POSS has a cubic cage structure, which can aggregate on the coating surface through surface migration. Its amino groups can also increase the epoxy crosslinking density and enhance the surface compactness, effectively hindering the entry of corrosive media while effectively improving the coating's hardness, hydrophobicity, and high-temperature resistance. At the same time, the introduced epoxy-modified organosilicon Mannich base also has a corrosion inhibitory effect, which can suppress the corrosion process of the impeller substrate.

[0017] This invention utilizes a nucleophilic addition reaction between diethylene glycol and isophorone diisocyanate to prepare a hydroxyl-terminated intermediate. Then, the hydroxyl-terminated intermediate undergoes a polyesterification reaction with glutaric acid to prepare a carboxyl-terminated low-polyester. Finally, the carboxyl-terminated low-polyester undergoes an amidation reaction with isophorone diamine to prepare a modified isophorone diamine curing agent. This modified isophorone diamine curing agent incorporates ether bonds, flexible chains, and amide bonds into the three-dimensional network structure of epoxy resin to achieve toughening and improved adhesion. By adding composite functional fillers and the modified isophorone diamine curing agent, this invention prepares a functional coating on the impeller substrate surface with high adhesion, strong hardness and impact resistance, while also possessing good hydrophobicity, corrosion resistance, and thermal crack resistance. Detailed Implementation

[0018] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0019] Example 1: A method for preparing octaaminophenyl POSS includes the following steps: (1) Add 135 mL of fuming nitric acid to the reactor, slowly add 20 g of octaphenyl POSS under ice bath, react at 0 °C for 30 min, then pour the reaction solution into 200 mL of ice water to obtain a light yellow precipitate, filter, wash with water until neutral, freeze dry to prepare octanitrophenyl POSS; (2) Add 2g of octanitrophenyl POSS and 0.2g of palladium on carbon to the reactor, add 40mL of tetrahydrofuran under nitrogen atmosphere, heat to 60℃ and react for 30min, then slowly add 20mL of hydrazine hydrate and continue the reaction for 12h. After the reaction is completed, filter with diatomaceous earth, concentrate the filtrate and add it to deionized water to obtain a white precipitate, filter and freeze dry to prepare octanitrophenyl POSS.

[0020] Example 2: A method for preparing a composite functional filler includes the following steps: A. Magnesium chloride and aluminum nitrate nonahydrate were dissolved in 50 mL of deionized water at a molar ratio of 2:1 to obtain a salt solution. Anhydrous potassium carbonate and deionized water were prepared at a mass ratio of 1:5 to obtain an alkali solution. The alkali solution was then slowly added dropwise to the salt solution. The mixture was refluxed at 100 °C and 300 r / min for 10 h. The pH value at the titration endpoint was adjusted to 11 by controlling the amount of alkali solution. After the reaction was completed, the mixture was centrifuged, washed, and dried to obtain magnesium-aluminum layered bimetallic hydroxide. B. Add 5.65g of paeonol, 3.15g of epichlorohydrin and 0.11g of benzyltriethylammonium chloride to the reactor, purge the air from the reaction system with nitrogen, heat to 100℃ under stirring and react for 4h, then cool to 60℃, add 1.44g of solid sodium hydroxide in batches over 1h and continue the reaction for 4h, wash with water until neutral after the reaction is completed, and distill under reduced pressure to prepare epoxy-modified paeonol; C. Under nitrogen protection, 6.64 g of 3-aminopropyltriethoxysilane, 3.51 g of paraformaldehyde, 6.67 g of epoxy paeonol and 100 mL of anhydrous ethanol were added to the reactor. The pH of the solution was adjusted to 5 using 15% hydrochloric acid. The temperature was raised to 60 °C and the reaction was continued for 6 h. After the reaction was completed, the solution was distilled under reduced pressure and recrystallized to prepare the epoxy-modified organosilicon Mannich base. D. Take 10g of magnesium-aluminum layered bimetallic hydroxide and 2.28g of epoxy-modified organosilicon Mannich base and add them to a mixed solution of 115mL of anhydrous ethanol and 90mL of deionized water. Stir the mixture at 75℃ for 7h. After the reaction is completed, filter, wash and dry to prepare modified magnesium-aluminum layered bimetallic hydroxide. E. Add 10g of modified magnesium-aluminum layered bimetallic hydroxide and 4.22g of octaaminophenyl POSS prepared in Example 1 to the reactor, then add 3.5g of N,N'-dicyclohexylcarbodiimide, 0.32g of benzyltriethylammonium chloride catalyst and 250mL of N,N-dimethylacetamide solvent. Stir and react at 140°C for 24h under a nitrogen atmosphere. After the reaction is completed, filter, wash and dry to prepare the composite functional filler.

[0021] Example 3: A method for preparing a modified isophorone diamine curing agent includes the following steps: ① Add 4.67 g of diethylene glycol and 50 mL of xylene to the reactor, stir and mix, then slowly add 4.45 g of isophorone diisocyanate, and stir and react at 80 °C for 4 h. After the reaction is completed, remove the solvent by rotary evaporation to prepare the terminal hydroxyl intermediate. ② Add 6.52g of hydroxyl-terminated intermediate and 2.63g of glutaric acid to the reactor, stir at 125℃ for 7h, and after the reaction is completed, take out the product and place it in a vacuum oven to remove moisture, thus preparing a carboxyl-terminated low polyester. ③ Add 7.25g of carboxyl-terminated low-polyester and 50mL of xylene to the reactor, stir and mix, then heat to 60℃, slowly add 7.79g of isophorone diamine, then heat to 80℃ and react for 3h. After the reaction is complete, heat to 165℃ and reflux to separate water. After anhydrous distillation, remove the solvent under reduced pressure to prepare the modified isophorone diamine curing agent.

[0022] Example 4 A functional coating comprises the following components in parts by weight: The mixture contained 62 parts of waterborne epoxy resin, 9.3 parts of the composite functional filler prepared in Example 2, 6.6 parts of the modified isophorone diamine curing agent prepared in Example 3, 0.4 parts of wetting agent polydimethylsiloxane, 0.2 parts of defoamer fatty alcohol polyoxyethylene ether, and 0.2 parts of leveling agent sodium polyacrylate.

[0023] A method for preparing a thermal crack resistant centrifugal compressor impeller material includes the following steps: Weigh each component according to the weight parts, and thoroughly stir the water-based epoxy resin, composite functional filler, wetting agent and leveling agent. Then add the modified isophorone diamine curing agent and defoamer and stir to obtain a functional coating. Then apply the functional coating to the surface of the polished AA2024 aluminum alloy impeller substrate, and cure at 120℃ for 2 hours, 150℃ for 2 hours and 180℃ for 2 hours to prepare the thermal crack resistant centrifugal compressor impeller material.

[0024] Example 5 A functional coating comprises the following components in parts by weight: The mixture contained 68 parts of waterborne epoxy resin, 12.5 parts of the composite functional filler prepared in Example 2, 10.2 parts of the modified isophorone diamine curing agent prepared in Example 3, 0.6 parts of wetting agent polydimethylsiloxane, 0.4 parts of defoamer fatty alcohol polyoxyethylene ether, and 0.4 parts of leveling agent sodium polyacrylate.

[0025] The preparation method of a thermal crack resistant centrifugal compressor impeller material is the same as in Example 4.

[0026] Example 6 A functional coating comprises the following components in parts by weight: 74 parts of waterborne epoxy resin, 14.7 parts of the composite functional filler prepared in Example 2, 13.8 parts of the modified isophorone diamine curing agent prepared in Example 3, 0.8 parts of wetting agent polydimethylsiloxane, 0.6 parts of defoamer fatty alcohol polyoxyethylene ether, and 0.7 parts of leveling agent sodium polyacrylate.

[0027] The preparation method of a thermal crack resistant centrifugal compressor impeller material is the same as in Example 4.

[0028] Comparative Example 1: A method for preparing a composite functional filler includes the following steps: A. Magnesium chloride and aluminum nitrate nonahydrate were dissolved in 50 mL of deionized water at a molar ratio of 2:1 to obtain a salt solution. Anhydrous potassium carbonate and deionized water were prepared at a mass ratio of 1:5 to obtain an alkali solution. The alkali solution was then slowly added dropwise to the salt solution. The mixture was refluxed at 100 °C and 300 r / min for 10 h. The pH value at the titration endpoint was adjusted to 11 by controlling the amount of alkali solution. After the reaction was completed, the mixture was centrifuged, washed, and dried to obtain magnesium-aluminum layered bimetallic hydroxide. B. Take 10g of magnesium-aluminum layered bimetallic hydroxide and 2.28g of 3-glycidyl etheroxypropyltrimethoxysilane and add them to a mixed solution of 115mL of anhydrous ethanol and 90mL of deionized water. Stir the mixture at 75℃ for 7h. After the reaction is completed, filter, wash and dry to prepare the modified magnesium-aluminum layered bimetallic hydroxide. C. Add 10g of modified magnesium-aluminum layered bimetallic hydroxide and 4.22g of octaaminophenyl POSS prepared in Example 1 to the reactor, then add 3.5g of N,N'-dicyclohexylcarbodiimide, 0.32g of benzyltriethylammonium chloride catalyst and 250mL of N,N-dimethylacetamide solvent. Stir and react at 140°C for 24h under a nitrogen atmosphere. After the reaction is completed, filter, wash and dry to prepare the composite functional filler.

[0029] Comparative Example 2: A functional coating comprises the following components in parts by weight: The mixture contained 74 parts of waterborne epoxy resin, 14.7 parts of the composite functional filler prepared in Comparative Example 1, 13.8 parts of the modified isophorone diamine curing agent prepared in Example 3, 0.8 parts of wetting agent polydimethylsiloxane, 0.6 parts of defoamer fatty alcohol polyoxyethylene ether, and 0.7 parts of leveling agent sodium polyacrylate.

[0030] The preparation method of a thermal crack resistant centrifugal compressor impeller material is the same as in Example 4.

[0031] Comparative Example 3: A functional coating comprises the following components in parts by weight: 74 parts of waterborne epoxy resin, 14.7 parts of magnesium-aluminum layered bimetallic hydroxide prepared in Example 2, 13.8 parts of modified isophorone diamine curing agent prepared in Example 3, 0.8 parts of wetting agent polydimethylsiloxane, 0.6 parts of defoamer fatty alcohol polyoxyethylene ether, and 0.7 parts of leveling agent sodium polyacrylate.

[0032] The preparation method of a thermal crack resistant centrifugal compressor impeller material is the same as in Example 4.

[0033] Comparative Example 4: A functional coating comprises the following components in parts by weight: The mixture contained 74 parts of waterborne epoxy resin, 14.7 parts of the composite functional filler prepared in Example 2, 13.8 parts of isophorone diamine curing agent, 0.8 parts of wetting agent polydimethylsiloxane, 0.6 parts of defoamer fatty alcohol polyoxyethylene ether, and 0.7 parts of leveling agent sodium polyacrylate.

[0034] The preparation method of a thermal crack resistant centrifugal compressor impeller material is the same as in Example 4.

[0035] Performance testing The performance of the thermal crack resistant centrifugal compressor impeller materials prepared in Examples 4-6 and Comparative Examples 2-4 was tested: (1) Adhesion test: The test was conducted in accordance with GB / T 9286-2021, and the data results are shown in Table 1.

[0036] (2) Hardness test: The test was conducted in accordance with GB / T 6739-2022, and the data results are shown in Table 1.

[0037] (3) Impact resistance test: The test was conducted in accordance with GB / T 1732-2020, and the data results are shown in Table 1.

[0038] (4) Contact angle test: The contact angle was measured at three different locations on the coating of the impeller substrate using a video optical contact angle meter with deionized water. The average value was calculated and the data results are shown in Table 1.

[0039] (5) Salt spray resistance test: The test was conducted in accordance with GB / T 10125-2021, and the data results are shown in Table 1.

[0040] (6) Heat crack resistance test: The sample was baked in an oven at 200℃ for 30 minutes, then cooled to room temperature and baked again. This was repeated 5 times. The coating was observed to see if cracks or wrinkles were produced. The data results are shown in Table 1.

[0041] Table 1 Sample performance test results Adhesion / Grade 0 0 0 0 0 1 Pencil hardness 4H 4H 4H 4H 2H 4H Impact strength / kg·cm 50 50 50 50 50 40 Water contact angle / ° 98.8 105.1 107.5 107.2 80.1 106.6 Salt spray resistance / d 70 72 73 61 45 70 thermal crack resistance No abnormalities in the coating No abnormalities in the coating No abnormalities in the coating No abnormalities in the coating Microcracks and wrinkles appeared in the coating. Microcracks and wrinkles appeared in the coating. As can be seen from the data in Table 1, the coatings prepared in Examples 4-6 of this invention have high adhesion, strong hardness and impact resistance, a water contact angle >90°, and hydrophobic properties, while also exhibiting good corrosion resistance and thermal cracking resistance. In Comparative Example 2, the composite functional filler replaced an equal amount of epoxy-modified organosilicon Mannich base with 3-glycidyl etheroxypropyltrimethoxysilane, and in Comparative Example 3, the composite functional filler replaced an equal amount with magnesium-aluminum layered bimetallic hydroxide. The measured salt spray resistance in Comparative Examples 2-3 was lower than that in Examples 4-6, and the decrease was more pronounced in Comparative Example 3 than in Comparative Example 2. This indicates that the grafting of epoxy-modified organosilicon Mannich base and octaaminophenyl POSS both improved the corrosion resistance of the coating to some extent. Simultaneously, the pencil hardness of Comparative Example 3 was measured... The hardness, water contact angle, and thermal crack resistance of the coating were lower than those of Examples 4-6, indicating that the introduction of composite functional fillers is beneficial to improving the hardness, hydrophobicity, and thermal crack resistance of the coating. In Comparative Example 4, the isophorone diamine curing agent was not modified, and its adhesion, impact strength, and thermal crack resistance were lower than those of Examples 4-6. This is because the introduction of ether bonds, flexible chains, amide bonds, etc. into the molecular structure of the isophorone diamine curing agent can effectively increase the flexibility and adhesion of the coating, thereby enhancing the impact toughness, adhesion, and thermal crack resistance of the coating.

[0042] In the description of this specification, references to terms such as "an embodiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. In this specification, illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.

[0043] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the claimed invention.

Claims

1. A thermally crack-resistant centrifugal compressor impeller material, characterized in that, The invention includes an impeller substrate and a functional coating applied to the surface of the impeller substrate. The functional coating comprises the following components in parts by weight: 60-75 parts of waterborne epoxy resin, 9-15 parts of composite functional filler, 6-14 parts of modified isophorone diamine curing agent, 0.3-1 part of wetting agent, 0.2-0.7 parts of defoamer, and 0.2-0.8 parts of leveling agent. The composite functional filler is prepared by grafting epoxy-modified organosilicon Mannich base with magnesium-aluminum layered bimetallic hydroxide, and then reacting the prepared modified magnesium-aluminum layered bimetallic hydroxide with octaaminophenyl POSS in a ring-opening reaction. The epoxy-modified organosilicon Mannich base is prepared by nucleophilic substitution reaction of paeonol with epichlorohydrin, and then prepared by Mannich reaction using 3-aminopropyltriethoxysilane, trioxymethylene and epoxy paeonol as raw materials. The modified isophorone diamine curing agent is prepared by nucleophilic addition reaction of diethylene glycol and isophorone diisocyanate, followed by polyesterification reaction of the prepared terminal hydroxyl intermediate with glutaric acid to prepare terminal carboxyl low polyester, and then amidation reaction of terminal carboxyl low polyester with isophorone diamine.

2. The thermal crack resistant centrifugal compressor impeller material according to claim 1, characterized in that, The impeller substrate is made of one of the following materials: aluminum alloy, stainless steel, titanium alloy, and nickel alloy.

3. The thermal crack resistant centrifugal compressor impeller material according to claim 1, characterized in that, The preparation method of the composite functional filler includes the following steps: A. Dissolve magnesium chloride and aluminum nitrate nonahydrate in deionized water to obtain a salt solution. Prepare an alkali solution using anhydrous potassium carbonate and deionized water. Slowly add the alkali solution to the salt solution and reflux at 100℃ and 300~400r / min for 10h. Adjust the pH value at the titration endpoint to 8~11 by controlling the amount of alkali solution. After the reaction is completed, centrifuge, wash and dry to prepare magnesium-aluminum layered bimetallic hydroxide. B. Add paeonol, epichlorohydrin and benzyltriethylammonium chloride to the reactor, purge the air from the reaction system with nitrogen, heat to 100°C under stirring and react for 4 hours, then cool to 60°C, add solid sodium hydroxide in batches over 1 hour and continue the reaction for 4 hours. After the reaction is completed, wash with water until neutral, and distill under reduced pressure to prepare epoxy-modified paeonol. C. Under nitrogen protection, 3-aminopropyltriethoxysilane, trioxymethylene, epoxy paeonol and anhydrous ethanol were added to the reactor. The pH of the solution was adjusted to 5 using 15% hydrochloric acid. The temperature was raised to 60℃ and the reaction was continued for 6 hours. After the reaction was completed, the solution was distilled under reduced pressure and recrystallized to prepare epoxy-modified organosilicon Mannich base. D. Add magnesium-aluminum layered bimetallic hydroxide and epoxy-modified organosilicon Mannich base to a mixed solution of anhydrous ethanol and deionized water, and stir at 65-80℃ for 6-8 hours. After the reaction is completed, filter, wash and dry to prepare modified magnesium-aluminum layered bimetallic hydroxide. E. Add modified magnesium-aluminum layered bimetallic hydroxide and octaaminophenyl POSS to the reactor, then add dehydrating agent N,N'-dicyclohexylcarbodiimide, catalyst benzyltriethylammonium chloride and N,N-dimethylacetamide solvent. Stir and react at 140°C for 24 h in a nitrogen atmosphere. After the reaction is completed, filter, wash and dry to prepare composite functional filler.

4. The thermal crack resistant centrifugal compressor impeller material according to claim 3, characterized in that, In step A, the molar ratio of magnesium ions to aluminum ions in the salt solution is 1~3:1; the mass ratio of anhydrous potassium carbonate to deionized water in the alkaline solution is 1:5~6.

5. The thermal crack resistant centrifugal compressor impeller material according to claim 3, characterized in that, In step B, the molar ratio of paeonol, epichlorohydrin, and benzyltriethylammonium chloride is 1:1:0.0142; in step C, the molar ratio of 3-aminopropyltriethoxysilane, paraformaldehyde, and epoxypaeonol is 1:1.3:

1.

6. The thermal crack resistant centrifugal compressor impeller material according to claim 3, characterized in that, In step D, the mass ratio of magnesium-aluminum layered bimetallic hydroxide to epoxy-modified organosilicon Mannich base is 10:1~3; in step E, the mass ratio of modified magnesium-aluminum layered bimetallic hydroxide to octaaminophenyl POSS is 10:3~5.

7. The thermal crack resistant centrifugal compressor impeller material according to claim 3, characterized in that, The preparation method of the octaaminophenyl POSS includes the following steps: (1) Add fuming nitric acid to the reactor, slowly add octaphenyl POSS under ice bath, react at 0°C for 30 min, then pour the reaction solution into ice water to obtain a pale yellow precipitate, filter, wash with water until neutral, freeze dry to prepare octanitrophenyl POSS; (2) Add octanitrophenyl POSS and palladium on carbon to the reactor, add tetrahydrofuran under nitrogen atmosphere, heat to 60℃ and react for 30 min, then slowly add hydrazine hydrate and continue the reaction for 12 h. After the reaction is completed, filter with diatomaceous earth, concentrate the filtrate and add it to deionized water to obtain a white precipitate, filter and freeze dry to prepare octanitrophenyl POSS.

8. The thermal crack resistant centrifugal compressor impeller material according to claim 1, characterized in that, The preparation method of the modified isophorone diamine curing agent includes the following steps: ① Diethylene glycol and xylene were added to the reactor, and after stirring and mixing, isophorone diisocyanate was slowly added dropwise. The mixture was stirred at 80°C for 4 hours. After the reaction was completed, the solvent was removed by rotary evaporation to prepare the terminal hydroxyl intermediate. ② Add the terminal hydroxyl intermediate and glutaric acid to the reactor, stir and react at 125~135℃ for 6~7h. After the reaction is completed, take out the product and place it in a vacuum oven to remove moisture, and prepare terminal carboxyl low polyester. ③ Add carboxyl-terminated low-polyester and xylene to the reactor, stir and mix, then heat to 60°C, slowly add isophorone diamine, then heat to 80°C and react for 3 hours. After the reaction is complete, heat to 150~180°C and reflux to separate water. After anhydrous distillation, remove solvent under reduced pressure to prepare modified isophorone diamine curing agent.

9. The thermal crack resistant centrifugal compressor impeller material according to claim 8, characterized in that, In step ①, the molar ratio of diethylene glycol to isophorone diisocyanate is 2.2~2.5:1; in step ②, the molar ratio of terminal hydroxyl intermediate to glutaric acid is 1:1.3; and in step ③, the mass ratio of terminal carboxyl oligoester to isophorone diamine is 0.8~1:

1.

10. A method for preparing a thermally crack-resistant centrifugal compressor impeller material according to any one of claims 1 to 9, characterized in that, The process includes the following steps: weighing each component according to weight, thoroughly mixing the water-based epoxy resin, composite functional filler, wetting agent, and leveling agent, then adding the modified isophorone diamine curing agent and defoamer and mixing to obtain a functional coating, then coating the functional coating onto the impeller substrate surface and curing it to obtain a thermal crack resistant centrifugal compressor impeller material; the wetting agent is polydimethylsiloxane; the leveling agent is sodium polyacrylate; and the defoamer is fatty alcohol polyoxyethylene ether or alkylphenol polyoxyethylene ether.